2019
DOI: 10.1021/acssuschemeng.9b03531
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles Alleviated the Bioavailability of Cadmium and Lead and Changed the Uptake of Iron in Hydroponically Grown Lettuce (Lactuca sativa L. var. Longifolia)

Abstract: Leafy vegetables are a rich source of iron and fibers for the human diet, which may become hazardous if exposed to heavy metal contamination. Cadmium (Cd) and lead (Pb) are two highly toxic metals even at trace concentrations. Engineered nanoparticles (ENPs) can alter the uptake of heavy metals and localization of essential minerals such as iron (Fe) through different mechanisms. The goal of this study was to understand the mutual effects of zinc oxide nanoparticles (ZnONPs) and coexisting heavy metals Pb 2+ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Metal-based NPs have also been shown to decrease the bioavailability of heavy metals to crop species. Sharifan et al (2019) demonstrated that ZnO NPs’ exposure reduced the Cd contents in lettuce roots and shoots by 49% and 30%, respectively [ 59 ]. Similarly, both bulk- and nano-sized TiO 2 NPs reduced the Pb accumulation in rice [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Metal-based NPs have also been shown to decrease the bioavailability of heavy metals to crop species. Sharifan et al (2019) demonstrated that ZnO NPs’ exposure reduced the Cd contents in lettuce roots and shoots by 49% and 30%, respectively [ 59 ]. Similarly, both bulk- and nano-sized TiO 2 NPs reduced the Pb accumulation in rice [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, ZnO NPs alleviated cadmium (Cd) toxicity in wheat by enhancing wheat growth and Zn concentrations, while reducing the Cd concentration in plants [ 27 ]. ZnO NPs alleviated the bioavailability of cadmium and lead and changed the uptake of iron in hydroponically grown lettuce ( Lactuca sativa L.) [ 31 ]. However, no related research has reported the effects of ZnO NPs on rice seedlings under chilling stress.…”
Section: Discussionmentioning
confidence: 99%
“…Soil is considered as a major sink of ZnO NPs compared to atmospheric and aqueous ecosystems (Liu et al 2020, Rajput et al 2018. In recent years, ZnO NPs have been employed as a novel macronutrient nanofertilizer in the Zn de cient soil (Song &Kim 2020, Sun et al 2020, Yuse -Tanha et al 2020, as an antibacterial agent for plant protection (Singh et al 2018), as well as an effective agent for reducing metal uptake by plants (Rizwan et al 2019, Sharifan et al 2019a. ZnO NPs may enter the soil medium by direct (agricultural products) or indirect (biosolids) pathways, and then can be absorbed and accumulated by plants, causing an effect on plant growth (Zeb et al 2021).…”
Section: Introductionmentioning
confidence: 99%